Readings in American educational thought : from Puritanism to progressivism - Milson, Andrew J.; Bohan, Chara Haeussler; Glanzer, Perry L.; Null, J. Wesley (Readings in educational thought., 2004)
The writings in this collection on American educational thought represent the many stories, individuals, and ideas that have shaped American education during the past several centuries. This book should serve as a useful primary or supplementary text for any undergraduate or graduate course in the history of American education, American educational thought, social foundations of education, philosophy of education, or curriculum theory. The editors of this volume hope that readers of this book will come to understand, and perhaps develop a desire to participate in, the "great conversation" that is American educational thought.